High copper concentrations produce genotoxicity and cytotoxicity in bovine cumulus cells - Anchordoquy, Juan Mateo (2017)
The aim of this study was to investigate the cytotoxic and genotoxic effects of high copper (Cu) concentrations on bovine cumulus cells (CCs) cultured in vitro.We evaluated the effect of 0, 120, 240, and 360 μg/dL Cu added to in vitro maturation (IVM) medium on CC viability assessed by the trypan blue (TB)–fluorescein diacetate (FDA) and 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assays, apoptosis, and DNA damage. Differences in cell viability assessed by TB–FDAwere not significant among CC treated with 0, 120, 240, and 360 μg/dL Cu. However, mitochondrial activity assessed by MTT was lower in CC cultured with 120, 240, and 360 μg/dL Cu as compared with the control (p < 0.01). Percentages of apoptotic cells were higher when CCs were treated with 120, 240, and 360 μg/dL Cu (p < 0.05) due to higher frequencies of late apoptotic cells (p < 0.05). The frequency of live cells diminished in a dose-dependent manner when Cu was added to the culture medium. Whereas genetic damage index (GDI) increased significantly in CC cultured in the presence of 240 and 360 μg/dL Cu (p ˂ 0.05), DNA damage increased at all Cu concentrations tested (p ˂ 0.05). These results indicate that Cu induces cytotoxic and genotoxic effects in bovine CC.